Apocynin ameliorates fumonisin b1 induced hepatotoxicity via NADPH oxidase inhibition and quantification of sphingosine and sphinganine - K. Krupashree; P. Rachitha; Farhath khanum (Elsevier, 2022)
Previous studies have shown that hepatotoxicity and NADPH oxidase mediated oxidative stress was activated by fumonisin 1 (Fb1) exposure, which is considered to be a critical event in the Fb1-induced toxic effect. However, the detailed mechanisms underlying Fb1-induced liver toxicity remain elusive. In this study, apocynin, a specific inhibitor for NADPH oxidase, was used to test suppression of ROS by inhibititing NADPH oxidase and it can protect against Fb1 induced hepatotoxicity in mice model and using HepG2 cell lines. In this context, the toxicity of Fb1 was examined in male albino mice. Apocynin with 25,50,100mg/kg b/wt was pretreated for 7 days oral administration. Fb1 2.25mg/kg b/wt was injected subcutaneously for 3 days. In mice model Fb1 injection induced oxidative stress by significant rise in serum marker enzymes and lipid peroxidation along with the reduction of antioxidant enzymes. Pretreatment of mice with different doses of apocynin (25,50,100mg/kg b/wt) significantly lowered AST, ALT and lipid peroxidation levels against Fb1 treated mice. Hepatic enzymes like SOD, CAT, GPx, GR, GSH were significantly increased by treatment with apocynin, against Fb1 treated mice. Fb1 perturbs sphingolipid metabolism by inhibiting ceramide synthase activity hence in the present study quantification of sphingosine and sphinganine quantified by LC MS analysis. In Fb1 injected mice samples the sphingoid bases elevated than normal pretreatment with apocynin reduced the sphingoid bases. The observed data demonstrates 50 % cell survival with 50 µM challenge for 24 h, which was restored to 90 % by pre-treatment with 100µM apocynin. It also decreased the lactate dehydrogenase leakage and preserved the cellular morphology. The DNA damage and nuclear morphology were assessed by comet assay and DAPI staining. Fb1 damaged DNA and nuclear morphology protected by apocynin pretreatment. The ultra-structural change induced by the Fb1 in cell lines, vacuolation was observed pre-treated cells with apocynin showed normal cell structure without vacuolation. On the Other hand, cell cycle distribution analysis showed cell cycle arrest at G0/G1 phase induced by Fb1 and its modulations was observed in apocynin pretreted cells. The protein expression CAT, GPx downregulated with Fb1 treatment and apoptotic markers caspase-3 and caspase-8 was upregulated. Pretretment with apocynin restored the antioxidant enzymes and overexpressed apocynin markers also altered. These findings suggest that apocynin ameliorates Fb1 induced hepatic damage via its antioxidant defence mechanism and might be used to treat oxidative stress mediated hepatic disorders.